Novel synthesis of divergent aryl imidazoles from ketones involving copper-catalyzed α-amination and oxidative C–C bond cleavage. Issue 23 (6th April 2020) - Huang, Jiangkun; Luo, Lan; Xing, Naiguo; Gu, Linghui; Li, Chen; Han, Qiao; Zheng, Shilong; He, Ling
Abstract : A one-pot synthesis, initiated by a copper salt with (NH4 )2 CO3 as the nitrogen source, forms divergent aryl imidazole derivatives from ketones via C–H activation, α-amination and oxidative C–C bond cleavage and condensation cascade reaction. Abstract : A one-pot synthesis, initiated by a copper salt with inorganic (NH4 )2 CO3 as the nitrogen source, forms divergent aryl imidazole derivatives from ketones via α-amination and oxidative C–C bond cleavage reactions. The approach provides a simple and rapid synthesis of imidazole derivatives and has certain versatility.